An Analysis of Beverage Size Restrictions - Brian A. Bourquard; Steven Y. Wu (Institute of Labor Economics (IZA), 2019)
Due to high levels of obesity, various government interventions have been proposed to curb the consumption of sugar-sweetened beverages (SSBs). The New York City "soda-ban," which proposed to limit the size of SSBs is among the most well-known and controversial. While public debates about beverage-size-restrictions tend to focus on how consumers are impacted, we use a nonlinear pricing model to show that, for all but extremely tight restrictions, consumer welfare would be unaffected by an enforceable restriction. However, sellers' profit would decline. While consumption is predicted to decline overall, the magnitude of the decline will vary by consumer segment.
Keywords: D82; I18; I31; 330; obesity; nonlinear pricing; health economics; beverage size restrictions; soda bans; sugar consumption